Legal Analysis of Preventive and Repressive Legal Protection for Pharmacy Personnel in Dealing with Drug Stockouts in Hospitals - Muhammad Zacky Aditya; Happy Yulia Anggraeni (Research Horizon, 2026)
Drug stockouts represent a significant systemic challenge in hospital healthcare systems, potentially generating severe legal consequences for pharmaceutical personnel. In practice, pharmacists frequently face a dilemma between their professional obligation to ensure the availability of medicines and the structural limitations of national pharmaceutical supply chains. This study aims to analyze preventive and repressive legal protections for pharmaceutical personnel in dealing with legal risks arising from drug stockouts in hospitals. The research employs a normative juridical method with statutory and case approaches, examining relevant regulations such as Law Number 17 of 2023 concerning Health, Minister of Health Regulation Number 73 of 2016 concerning Pharmaceutical Service Standards in Hospitals, and related court decisions. The results indicate that preventive legal protection for pharmacists remains insufficient due to the absence of clear regulatory mechanisms defining professional responsibility during force majeure conditions, such as supply chain disruptions. Meanwhile, repressive protection largely depends on judicial interpretation regarding negligence and the causal relationship between drug stockouts and patient harm. Therefore, a comprehensive legal protection model is required, encompassing standardized stock management procedures, strengthened pharmaceutical governance in hospitals, and the formal recognition of the force majeure doctrine within health law as a legitimate legal defense for pharmaceutical personnel.